Comparative analysis of the overall level of preparedness of Dental graduates for their cognitive, communication, and professional skills in terms of offline and online education: a non-randomized controlled trial - Aditi Verma; Pramila M; Geetha Sandur (Revista Sul-Brasileira de Odontologia, 2025)
The recent pandemic has led to the suspension of offline training and the exploration of distant learning methods. Objective: This paper aims to identify and compare the overall level of preparedness of dental graduates for their cognitive, communication, and professional skills in terms of offline and online educational methods from students’ perspectives. Material and methods: A web-based non-randomized longitudinal trial was conducted amongst 182 students pursuing their final year in a dental college in Bangalore City, India for the academic years 2020-21 Study Group (Exposure to only online teaching) and 2021- 22 Control Group (Exposure to both online and Classroom-based teaching). A Pre-tested online questionnaire was used to evaluate the change in the assessment of educational experience and the level of preparedness of dental graduates for cognitive, communication, and professional skills for the academic batch 2020-21 and then for 2021-22. Results: The study group missed educational experiences more as a result of the lockdown than the control group (p<0.05) but considered online assessment as a good evaluation method (p<0.05). Clinical Training is perceived as most affected by distant learning methodology. Moreover, the study group felt a greater need to be mentored or indirectly supervised following graduation (p<0.05) despite reporting almost similar self-perceived preparedness levels. Conclusion: Online Education has shown similar preparedness levels among dental graduates for cognitive, communication, and professional skills making it a promising alternative methodology for offline education. However, there are a few uncertainties regarding clinical practice so; a “Smart Hybrid Model” of educational approach for dental education should be promulgated.